PROFIL KADAR KREATININ DAN ASAM URAT SEBAGAI PENANDA FUNGSI GINJAL PADA PENDUDUK LANSIA DI DESA KETEWEL - I.N. Wande; I.G.A.D. Ratnayanti; I.G.K.N. Arijana; N.M. Linawati; P.P.A.P. Dewi (Buletin Udayana Mengabdi, 2023)
Background. Elderly is a group of population aged 46 years and over based on the age category according to the Ministry of Health of the Republic of Indonesia 2009. The function of the body's organs of the elderly population will decrease over time, especially kidney function. Several laboratory tests that can be used to assess kidney function are measuring the glomerular filtration rate or measuring levels of non-protein nitrogen such as creatinine and uric acid. Objectives. To determine kidney health in the elderly population in Ketewel Village by measuring blood creatinine and uric acid levels and providing education to keep the kidneys healthy. Implementation method. Elderly residents were given information about free kidney function tests, namely uric acid and blood creatinine, then directed to the Mantra Medika Clinical Laboratory for blood collection to avoid crowds due to the Covid-19 pandemic situation. Examination of blood creatinine and uric acid with the Erba XL100® device. Results. There were 22 elderly residents of Ketewel Village who did free creatinine and blood uric acid test. A total of 11 elderly men and 11 elderly women who participated in this program. The average age of the elderly who underwent examination was 59.95 ± 9.04 years. The mean systolic blood pressure was 127 ± 15 mmHg. The mean diastolic blood pressure was 76 ± 9.5 mmHg. The mean blood creatinine level was 0.95 ± 0.2 mg/dl. The average blood uric acid level was 5.42 ± 0.92 mg/dl. Conclusion. Free examination Creatinine and blood uric acid levels in the elderly population in Ketewel Village are within normal limits which can indicate kidney function of the elderly population is still within normal limits. Keywords: Creatinine, uric acid, elderly, Ketewel Villag